2018
DOI: 10.3389/fmicb.2018.02566
|View full text |Cite
|
Sign up to set email alerts
|

Differentiated Mechanisms of Biochar Mitigating Straw-Induced Greenhouse Gas Emissions in Two Contrasting Paddy Soils

Abstract: Straw returns to the soil is an effective way to improve soil organic carbon and reduce air pollution by straw burning, but this may increase CH4 and N2O emissions risks in paddy soils. Biochar has been used as a soil amendment to improve soil fertility and mitigate CH4 and N2O emissions. However, little is known about their interactive effect on CH4 and N2O emissions and the underlying microbial mechanisms. In this study, a 2-year pot experiment was conducted on two paddy soil types (an acidic Utisol, TY, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
23
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 92 publications
4
23
0
Order By: Relevance
“…Soil properties in 2016 have been presented in our previous work (Table S1) (Wang et al, 2018b), and the results of 2017 were similar to that of 2016. In 2017, soil pH ranged between 8.4 to 8.6 in the BH soil (Inceptisol) with no significant difference among the treatments, while pH in the TY soil was significantly increased by 0.8-1.0 unit after one-year rice plantation, compared with the newly flooded N0 treatment (pH at 6.4) in 2017 (Table 1).…”
Section: Soil Physiochemical Properties During Rice Growing Periodssupporting
confidence: 79%
See 2 more Smart Citations
“…Soil properties in 2016 have been presented in our previous work (Table S1) (Wang et al, 2018b), and the results of 2017 were similar to that of 2016. In 2017, soil pH ranged between 8.4 to 8.6 in the BH soil (Inceptisol) with no significant difference among the treatments, while pH in the TY soil was significantly increased by 0.8-1.0 unit after one-year rice plantation, compared with the newly flooded N0 treatment (pH at 6.4) in 2017 (Table 1).…”
Section: Soil Physiochemical Properties During Rice Growing Periodssupporting
confidence: 79%
“…In addition, we found that nrfA gene abundance significantly decreased over time in 2016, indicating a declined effect from straw incorporation. Considering the facts that rice straw amendment could effectively improve DNRA while high N input had reverse effect on DNRA as observed in this study and above mentioned studies, together with our previous finding that straw amendment had potential risk in enhancing N 2 O emission in the same soils (Wang et al, 2018b), we recommended that simultaneous application of both nitrogen fertilizers and rice straws should be avoided in paddy rice fields.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…The FTIR results of RHB indicated that the presence of the carboxyl group (COOH), OH −, and NH 2 (Singh & Gautam, 2017) could be beneficial to enhance soil elemental status (Ding et al, 2016) compared to inorganic fertilizer. The biochars derived from CRs contain elemental nutrient contents useful for paddy plants and provides shelter for micro‐flora (Wang et al, 2018; Warnock et al, 2010). The porous quality, larger internal surface area, ability to adsorb soluble organic matter and inorganic nutrients (Singh et al, 2018) of RHB could be a potential soil amendment for paddy agriculture.…”
Section: Resultsmentioning
confidence: 99%
“…In all, 1,296 gas samples were collected and measured. Calculation of N2O flux was performed via a linear regression model (Wang et al, 2018b),…”
Section: Gas Sampling and N2o Measurementmentioning
confidence: 99%